PERENCANAAN PORTAL BETON BERTULANG PADA GEDUNG PKP-PK BARU DI BANDAR UDARA DEPATI PARBO KERINCI - Shopy Mellyana; Fahrur Rozi; Linda Winiasri (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Depati Parbo Kerinci Airport is located in Hiang Tinggi Village, Sitinjau Laut District, Kerinci Regency, Jambi. The airport has a runway with a length of 1800 meters and a width of 30 meters. Depati Parbo Kerinci Airport is starting work on developing the airport, which was originally located in Koto Baru Hiang, will be rebuilt in Koto Iman with an area of ​​4 hectares using the same runway. One of these developments is the construction of a new Aviation Rescue and Firefighting Building. The construction of the Aviation Rescue and Firefighting Building as an aviation accident relief building and aircraft fire suppression is also a very important infrastructure in the airport area. Planning for the new Aviation Rescue and Firefighting Building at Depati Parbo Airport Kerinci was carried out in order to be able to plan part of every detail of the concrete portal planning for the new Aviation Rescue and Firefighting Building using the Special Moment Resistant Frame System (SRPMK) because Kerinci Jambi district is an area that has an earthquake strength of 1.5 – 2.0 g entering the high earthquake zone. In the construction of PKP-PK assisted using SAP 2000 software which can help make buildings earthquake resistant. With the results of this planning, the dimensions of the beam structure 1 30 cm x 30 cm, beam 2 20 cm x 25 cm, plate thickness 12 cm, column 1 20 cm x 20 cm, column 2 30 cm x 30 cm, and the construction of the Aviation Rescue and Firefighting Building are obtained requires a fee of Rp. 337,2490,000.00 which is counted as Three Hundred Thirty Seven Million Two Hundred Emat Twenty Nine Thousand Rupiah.